Assessment of patients' psychological state and self-efficacy associated with postoperative constipation after thoracolumbar fracture surgery. Issue 9 (September 2019) - Jing, Deng; Jia, Li
Objective: We aimed to explore the relationship among the duration of constipation at 30 days after thoracolumbar fracture surgery, self-efficacy, and anxiety or depression in patients with constipation after thoracolumbar fracture surgery. Methods: In this descriptive correlational study, 108 patients with thoracolumbar fracture undergoing pedicle screw fixation surgery were recruited from January 2015 to May 2017 in our hospital. From the day of surgery, we conducted a 1-month follow-up investigation. We evaluated the pattern of defecation, stool consistency, and incidence of defecation-related problems using a structured interview. Clinical data were obtained using a patient intake form, and we applied the Health Behavior Self-Efficacy Scale (HBSES), and Hospital Anxiety and Depression Scale (HADS). Results: Approximately 83.3% of patients experienced postoperative constipation, and most exhibited normal defecation by postoperative day 13. Self-efficacy and anxiety and depression were graded at a medium level in most patients. The average HBSES score was 74.39 ± 11.08, and the mean HADS score was 7.97 ± 4.08. The duration of postoperative constipation was negatively correlated with self-efficacy and positively associated with anxiety or depression. Conclusions: Self-efficacy, anxiety, and depression are important sociopsychological factors associated with the duration of postoperative constipation.